Escherichia coli inner membrane display system for high‐throughput screening of dimeric proteins. Issue 12 (25th September 2018) - Jo, Migyeong; Hwang, Bora; Yoon, Hyun Woung; Jung, Sang Taek
Abstract: Multimer formation is indispensable to the intrinsicbiologicalfunctions of many natural proteins. For example, the human immunoglobulin G (IgG) antibody has two variable regions (heavy chain variable domain [VH] and light chain variable domain [VL]) that must be assembled for specific antigen binding, and homodimerization of the antibody's Fc domain is essential for eliciting therapeutic effector functions. For the more efficient high‐throughput directed evolution of multimeric proteins with ease of cultivation and handling, here we report a membrane protein drift and assembly (MPDA) system, in which a multimeric protein is displayed on a bacterial inner membrane by drifting and auto‐assembling membrane‐anchored subunit polypeptides. This system enabled the auto‐assembly of membrane‐tethered Fv domains (VH and VL) or the monomeric Fc domain into a functional hetero‐ or homodimeric protein complex on the bacterial inner membrane. This system could also be used to enrich a desired engineered Fc variant from a mixture containing a million‐fold excess of wild‐type Fc domain, indicating the applicability of the MPDA system for the high‐throughput directed evolution of a variety of multimeric proteins, such as cytokines, enzymes, or structural proteins. Abstract : In this work, we present membrane protein drift and assembly (MPDA) system, an efficient functional E. coli display technique for high throughput screening of homo‐ and heteromultimeric proteins. Polypeptides expressed on the fluidic lipid bilayer inner membrane can be drifted to display functional auto‐assembled multimeric proteins and we demonstrated the utility of the system using homodimeric IgG Fc and heterodimeric bevacizumab VH‐VL display. This novel display system will be an excellent resource for engineering multimeric proteins.